Web 2.0 at the University of Huelva. Educational styles use - Boza Carreño, Ángel; Conde Vélez, Sara (Revista Complutense de Educación, 2016)
The work presented below focuses on the analysis of styles of education use that students make use of the Web 2.0 in order to promote the knowledge and benefits of these and make proposals that favor the incorporation and use of tools Web 2.0. For data collection an ad hoc scale on a sample of 403 students from different courses at the University of Huelva is applied. For the treatment of the data, a multiple correspondence analysis is made. From the results, three styles of educational use are identified among students of the University of Huelva: 1) Style focused on individualistic and autonomous work; 2) Style focused on the utility and positive aspects of the Web 2.0; and 3) Style focused on the impact of the Web 2.0 and difficulties encountered. It is undeniable that the use of the Web 2.0 enables positives aspects.
Keywords: Training; use; impact; Web 2.0; higher education